The Effect of Pretreatment Potential Resistance to NNRTIs on Antiviral Therapy in Patients With HIV/AIDS. (1st October 2022) - Li, Cui-Lin; Liang, Hong-Yuan; Xiao, Jing; Li, Rui; Yu, Feng-Ting; Zeng, Yong-Qin; Pang, Xiao-Li; Wang, Di; Liu, Ying; Li, Bei; Han, Jun-Yan; Zhao, Hong-Xin
Abstract : Background: With the increasing coverage of antiretroviral therapy, concerns for the emergence and transmission of HIV drug resistance (HIVDR) are arising. HIVDR was divided into 5 levels: sensitive, potentially resistant, low resistant, intermediate resistant, and high resistant. Most of the articles on HIVDR involved low-level, intermediate-level, and high-level drug resistance to antiretroviral drug, and few articles deal with potential drug resistance. Treatment failure associated with the level of low-level, intermediate-level, and high-level resistance to antiretroviral drug has been reported. However, whether virological failure (VF) is related to potential resistance remains unclear. In this study, we aimed to describe the situation of potential resistance to antiretroviral drug and whether it is related to VF. Methods: We analyzed the demographic, behavioral information, medical history, and drug resistance–associated mutation data from subjects. Drug resistance mutations at baseline and time of failure in patients suffering VF were detected by using the Vela automated next-generation sequencing platform. The χ 2 test or Fisher exact test and logistic regression were used to assess the risk factors that contribute to VF in the potential drug-resistant people. Results: The prevalence of overall pretreatment drug resistance was 7.06% (233/3300), and the prevalence of pretreatment potential resistance was 8.79% (290/3300). All these patients with pretreatment potential first-line drugs resistance showed potential resistance to nonnucleoside reverse transcriptase inhibitors (NNRTIs), and some of them had potential drug resistance to NNRTIs and NRTIs or NNRTIs and PIs; among these patients, 94.71% (179/189) had V179 D/E mutations. The VF rate of first-line treatment for potentially resistant people is 17.99%. CD4 + T-cell count ≤200 cells/L at antiretroviral therapy initiation are risk factors for the failure of first-line treatment. Conclusions: The prevalence of potential drug resistance among individuals with HIV and the VF rate of first-line treatment for potential drug-resistant people were high. To better optimize clinical management, prevention, and control of HIV, attention should be devoted to the potential resistance of nonnucleoside drugs.